Psychological characteristics of professional retraining of adults - RUDENKO, Alexandra (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the study of psychological characteristics of professional retraining of adults. The characteristic features of professional retraining of adults, who are gaining the second higher education, are established on the basis of theoretical analysis and the results of empirical research. The author emphasizes that there exists a number of essential distinctions between professional self-actualization of young people and adults